2020
DOI: 10.1093/bjsw/bcaa034
|View full text |Cite
|
Sign up to set email alerts
|

The Social Work Regulator and Professional Identity: A Narrative of Lord and Bondsman

Abstract: Since the early 2000s, in a development since mirrored throughout much of the Anglophone world, social work across UK jurisdictions has been subject to external regulation. Whilst a key justification for regulation was to enhance professional identity, there is little evidence that it has done so. Indeed, a growing literature points out conflictual and unproductive relationships between the social work profession and its regulators, within which a marked power imbalance in favour of the regulator is apparent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This contrasts strongly with the “doctor knows best” narratives commonly associated with medical professionals (Lindsey, 2020). Social work researchers have forwarded the position that their profession in the UK is “under attack” from central government with occasional support from the public facilitated by discourses in the media (McKendrick and Finch, 2016; Simpson et al , 2020). In 2022, the social work community received publication of another government commissioned independent report into the suitability of social work practice with children which included recommendations to enhance rigour in both initial training and ongoing professional development (McAlister, 2022).…”
Section: Background and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts strongly with the “doctor knows best” narratives commonly associated with medical professionals (Lindsey, 2020). Social work researchers have forwarded the position that their profession in the UK is “under attack” from central government with occasional support from the public facilitated by discourses in the media (McKendrick and Finch, 2016; Simpson et al , 2020). In 2022, the social work community received publication of another government commissioned independent report into the suitability of social work practice with children which included recommendations to enhance rigour in both initial training and ongoing professional development (McAlister, 2022).…”
Section: Background and Contextmentioning
confidence: 99%
“…In 2022, the social work community received publication of another government commissioned independent report into the suitability of social work practice with children which included recommendations to enhance rigour in both initial training and ongoing professional development (McAlister, 2022). This report follows over 20 years of central government’s “reviews” of social work each with its own recommendations for making social work training more fit for practice (Simpson et al , 2020). Critics (and defenders of social work) argue that such reviews are an attempt by government to link the practice of social work with the cause of persistent injustices in society (Brindle, 2013) thereby providing society with both scapegoats and tangible solutions (Hanley, 2019).…”
Section: Background and Contextmentioning
confidence: 99%
“…Yet, its merits notwithstanding, ongoing debates about how regulation should be implemented are common issues among countries. Issues such as the powers given to regulatory bodies, the political nature of regulation, disconnects between educational and regulation systems, and regulation assessments remain topics of debate (Apgar, 2019; Simpson et al, 2020; Worsley et al, 2020). Thus, a global review provides a broader understanding of challenges countries may experience when situating a regulatory framework within a specific context, such as the UAE.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The usefulness of licensure includes assurances to clients that a professional social worker has met the standards of the professions for practice and competency within a specific context, and usually encompasses some form of examination and ongoing professional development requirements (Miller et al, 2015). In the United Kingdom, Canada, Ireland, New Zealand, South Africa, and others, a similar yet distinct state-sanctioned process referred to as registration, uses registry lists and formalized registration procedures (Breda & Addinall, 2021; Simpson et al, 2020; Worsley et al, 2020). Registration involves an application to a government or public entity and often a fee, but does not necessarily include an examination, although clinical social workers typically do sit for an exam (Breda & Addinall, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gibson (2019) found that historical incidents of social workers being 'named and shamed' continue to encourage professionals to regulate their identities in ways that conform to institutional and government set standards (2019: 117). Furthermore, there are a number of professional processes that have been identified as instilling fear in social workers in ways that encourage obedience and hamper collective action, including positivist models of risk assessment (Littlechild, 2008), professional regulation (Simpson et al, 2020), service inspections (Gibson, 2019), and fitness to practice proceedings (FTPP) (Kirkham et al, 2019). Many, if not most, social workers will support these various processes, safe in the belief that they are there to protect against problematic social workers, or the aforementioned 'other people'.…”
Section: Social Movements Of Hopementioning
confidence: 99%